Evaluation of water balance in a population of older adults. A case control study. (April 2018) - Malisova, Olga; Poulia, Kalliopi-Anna; Kolyzoi, Kleoniki; Lysandropoulos, Athanasios; Sfendouraki, Kalliopi; Kapsokefalou, Maria
Summary: Older adults are at risk for dehydration and its' potentially life-threatening consequences. Unrecognized dehydration can complicate chronic medical problems and increase morbidity. The objective of the study was to estimate water balance, intake and loss in elderly people living in Greece using the Water Balance Questionnaire (WBQ). WBQ was administered in winter to 108 independents (65–81yrs) (Group A), 94 independents (82–92yrs) (Group B) and 51 hospitalized (65–92yrs) (Group C). A database from previous study of 335 adults (18–65yrs) (Control Group) used for comparison. Mean estimates of water balance, intake and loss were, respectively, for Group A −749 ± 1386 mL/day, 2571 ± 739 mL/day and 3320 ± 1216 mL/day, for Group B −38 ± 933 mL/day, 2571 ± 739 mL/day and 3320 ± 1216 mL/day, for Group C 64 ± 1399 mL/day, 2586 ± 1071 mL/day and 2522 ± 1048 mL/day and for Control Group −253 ± 1495 mL/day, 2912 ± 1025 mL/day and 3492 ± 2099 mL/day. Significant differences were detected in water balance, intake and loss (p < 0.01). Water balance and water intake in Group A was the lowest. For Groups A, B, C and Control, contribution of solid foods to water intake was 36%, 29%, 32%, 25%, of drinking water was 32%, 48%, 45%, 47%, of beverages was 32%, 23%, 23% and 28% respectively. Significant differences observed in the contribution of drinking water and beverages (p < 0.01). Group A had lower water balance and water intake. Groups B and C had lower water intake from beverages.